The potential soil organic carbon stocks in mangrove areas of Sinjai District, South Sulawesi, Indonesia - Abdul Malik; Muhammad Ichsan Ali; Suwardi Annas; Abdul Rasyid Jalil; Restu Utami Mulya; Konstantina Gravani (Journal of Environmental Engineering and Landscape Management, 2022)
The soil pool is the primary sink for carbon in mangrove wetlands and plays a major role in mitigating climate change. However, aquaculture pond expansions go further to disrupt carbon storage in mangroves. The aim of this study is to estimate the stock of soil organic carbon (SOC) in the mangrove area of South Sulawesi, Indonesia. The mangroves of Sinjai District in South Sulawesi are a disturbed region with no previous study on SOC stock. We implemented a line transect method at five study sites, collected 15 soil cores at a depth of 0–15 cm, 15–30 cm, and 30–50 cm, and performed soil analysis using the Loss on Ignition method. We find that the mean value of SOC stock is 413.10±12.37 Mg C ha–1. More attention to the conservation and restoration of lost mangrove areas is a high priority. It may also increase the stock of SOC to mitigate climate change. This study will help to preserve the remaining mangroves.